PHANE‐TetraPHOS, the First D2 Symmetric Chiral Tetraphosphane. Synthesis, Metal Complexation, and Application in Homogeneous Stereoselective Hydrogenation. Issue 17 (5th May 2021) - Vaghi, Luca; Cirilli, Roberto; Pierini, Marco; Rizzo, Simona; Terraneo, Giancarlo; Benincori, Tiziana
Abstract: PHANE‐TetraPHOS, a new D 2 symmetric tetraphosphane based on the [2.2]paracyclophane scaffold, has been synthesized and characterized. The peculiarity of this system is the presence of four homotopic diphenylphosphane groups, exchangeable through C2 symmetry operations and consequently indistinguishable. Their spatial arrangement allows the simultaneous complexation of two metal atoms. Enantiomeric purity was attained at tetra‐phosphane oxide level by fractional crystallization of the diastereomeric adducts obtained from the racemate with enantiopure dibenzoyltartaric acids. Alkaline treatment of diastereomerically pure adducts followed by exhaustive P−O groups reduction with HSiCl3 gave both PHANE‐TetraPHOS antipodes in an enantiopure state. They were tested as rhodium ligands in the homogeneous enantioselective hydrogenation of some benchmark unsaturated compounds. Catalytic activity and enantiodiscrimination ability were found comparable to those exhibited by the complexes of the parent bidentate ligand PHANEPHOS, but only half a mole of precious chiral ligand was employed. Abstract : The new chiral phosphane ligand PHANE‐TetraPHOS displays an unusual D2 symmetry with four homotopic diphenylphosphane groups exchangeable through C2 symmetry operations. This structure allows the simultaneous complexation of two metal atoms without any strain allowing synchronous operations of the two active centres in homogeneous asymmetric catalysis.